Reframing adolescent research - Hendry, Leo B.; Kloep, Marion, 1955- (Abingdon, Oxon ; New York, NY : Routledge, 2019)
How can we ensure that adolescent research is really assisting the optimal developmental transitions of young people, now and in the near future? Reframing Adolescent Research suggests that what is needed is a 'paradigm-shift', a movement towards implementing more systemic, innovative and inter-disciplinary approaches to youth research, which are more suited to resolving the real issues that young people face in the twenty-first century. Contributions from world-class academics examine theoretical concerns and methodological challenges to substantive areas in the field, considering possible limitations and weaknesses in current approaches. They argue for the need for 'unorthodox,' systemic inter-disciplinary research which looks beyond the social sciences to consider innovations and novel approaches to the study of adolescence and development across the lifespan. New theories, methods and interventions are presented that are essential to advancing the project of understanding adolescents and how they develop on a global stage.This ground-breaking volume will encourage debate and dialogue on the future of youth research. It is valuable reading for advanced students and researchers in adolescent development and developmental psychology.
'To boldly go!' reframing adolescent research -- An idiographic approach to adolescent research: theory, method, and application -- An elaboration of non-linear, non-ergodic, and self-organizing processes: understanding the bumps and jumps in adolescent development -- Longitudinal methods in adolscent psychology: where could we go from here? and should we? -- Using contextual action theory for conceptualization and research on adolescent development -- The challenge of the brain: what can the new adolescent neuroscience tell us, what are its limits, and where could it go from here? -- Breaking disciplinary boundaries? an example from toxicology: endocrine disruptor chemicals and adolescents -- A social psychologists' perspective on future directions: the many faces of Youth Studies -- Epilogue: 'beam me up, Scottie!' -- Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: Adolescent psychology -- Research -- Methodology; Adolescence -- Research -- Methodology; Adolescence -- Recherche -- Méthodologie.; FAMILY & RELATIONSHIPS / Life Stages / General; PSYCHOLOGY / Developmental / General; PSYCHOLOGY / Developmental / Lifespan Development; PSYCHOLOGY / General